EVALUATING STRATEGIC EDUCATIONAL PLANNING PRACTICES AT THE MINISTRY OF EDUCATION IN THE SULTANATE OF OMAN تقىَى يًارساث انتخطُظ انتزبىٌ اإلستزاتُجٍ بىسارة انتزبُت وانتعهُى فٍ سهطُت عًاٌ - Khalfan Said Al-Rawahi, Said; Ahmed Mohamed, Ismaiel Hassanein; Salleh, Mohamad Johdi (2020)
The current study aimed to identify the reality of planning practices for workers in educational planning agencies in the Ministry of Education in the Sultanate of Oman. The problem arose out of the existence of many aspects of deficiency and shortcomings in the exercise of the planning tasks assigned to them in these bodies, in addition to the presence of other problems experienced by these devices, which limit the efficiency and effectiveness of workers to exercise the tasks assigned to them. To achieve the objectives of the study, a questionnaire was formed consisting of (50) items, which were classified according to four axes represented by planning practices for workers in educational planning agencies, namely: tasks of educational planning agencies, administrative organization, planning cadres, educational information. The study sample consisted of (208) individuals with positions: department manager, deputy director, head of department, and a technical member in the planning departments of the Ministry and educational governorates in the Sultanate of Oman, and statistical processing of data was carried out using arithmetic averages, standard deviations and rank. The results of the study showed: The planning practices of workers in educational planning agencies in the four fields of study: tasks of planning organs, administrative organization, planning cadres, educational information were of a moderate degree.